The Correlation Between Students’ Learning Anxiety and Speaking Skills in Lower Secondary School - Dessy Mutiara Syahbani; Tri Wintolo Apoko (Journal of Languages and Language Teaching, 2023)
Speaking skill, which involves the ability to communicate orally, demands self-confidence and composure when interacting with others. Furthermore, speaking in the English language poses a significant challenge for many students, often inducing nerves and anxiety. The purpose of this research was to examine the correlation between students' learning anxiety and their speaking skills at the lower secondary school level. To investigate this relationship, a quantitative research approach with a correlation design was adopted. The data collection involved the administration of a questionnaire (FLCAS) to assess students' learning anxiety and an English-speaking test to evaluate their speaking skills. The questionnaire used in this study was adapted from the work of Horwitz et al. (1986) to measure students' learning anxiety. The collected data were analyzed using the SPSS Program version 25. The target population for this English-speaking of all second-grade students, totaling 102 individuals. Through simple random sampling, 41 students were selected as respondents. The analysis of the data yielded results indicating the acceptance of the alternative hypothesis (Hi) and the rejection of the null hypothesis (H0) (0.046 < 0.05). Thus, the findings suggest a significant correlation between students' learning anxiety and their speaking skills. In summary, the research findings support the existence of a relationship between students' learning anxiety and their proficiency in speaking skills. The study contributes to the understanding of the challenges faced by students in developing their speaking abilities, particularly in the context of English language learning.